SOSIALISASI DAN EDUKASI PEMANFAATAN TANAMAN BERKHASIAT OBAT DAN MAKANAN SEHAT DALAM MENINGKATKAN SISTEM IMUNITAS DI ERA NEW NORMAL - Novandi Purba; Nur Ulina Turnip; Amina Syarifuddin; Khairil Akbar (JURNAL PENGMAS KESTRA (JPK), 2021)
Medicinal plants that can boost the immune system are very much consumed by the public, especially during the current COVID-19 pandemic. Apart from plants, healthy food also has an important role in improving the immune system in this new normal era, one of which we must consume balanced nutritious foods such as staple foods, namely rice, corn, tubers and side dishes as well as vegetables and fruit. Fruits are a source of protein, minerals, fiber and vitamins. In addition, to face new changes requires careful preparation. Health quality is the main component to face the transition from the Covid-19 era to change for the better. Therefore, it is necessary to maintain the body's immune system which is the body's defense to ward off various diseases. The body's immune system can be improved by changing a bad lifestyle. Including physical exercise (sports). The purpose of Community Service (PKM) is to assist the local government in increasing public awareness to prevent and fight the Covid-19 virus in the form of utilizing nutritious plants that can increase the body's immune system and eat healthy food. The activity was carried out in the form of online discussions through whatsapp groups and meetings via zoom with the younger generation of Lubuk Pakam. From this activity, the younger generation has gained a good understanding of what to do in the new normal era, not only complying with health protocols, but also in regulating lifestyle and eating patterns.